1999
DOI: 10.1136/jnnp.67.6.710
|View full text |Cite
|
Sign up to set email alerts
|

Does the extent of axonal loss and demyelination from chronic lesions in multiple sclerosis correlate with the clinical subgroup?

Abstract: Objective-To determine non-invasively the relation between the degree of axonal loss and the extent of demyelination in chronic lesions visible on MRI in patients with diVerent subgroups of clinically definite multiple sclerosis using 1 H magnetic resonance spectroscopy ( 1 H MRS) and magnetisation transfer imaging (MT). Conventional MRI is unable to diVerentiate between the various pathological processes occurring in the multiple sclerosis lesion. There are, however, newer MR techniques which show promise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 36 publications
(22 reference statements)
5
41
0
Order By: Relevance
“…To have a comprehensive picture of the patients studied, we also investigated the possible structural correlates of fMRI abnormalities in these patients, by assessing global brain damage, in terms of T 2 -visible lesions, brain volume, NAWM and GM involvement, and regional damage of WM fiber bundles variously related with the cognitive tasks investigated. In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…To have a comprehensive picture of the patients studied, we also investigated the possible structural correlates of fMRI abnormalities in these patients, by assessing global brain damage, in terms of T 2 -visible lesions, brain volume, NAWM and GM involvement, and regional damage of WM fiber bundles variously related with the cognitive tasks investigated. In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Since, as the majority of the quantitative MRI studies in BMS provided conflicting results [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996Filippi et al, , 1999Filippi et al, , 2000Horsfield et al, 1996;Traboulsee et al, 2003], we expanded the widely used approach of quantification of NAWM and GM damage by assessing the extent of damage of several WM fiber bundles, by means of MR tractography. In addition, to test whether brain plasticity in these patients is elicited by damage of tracts specifically related to the performance of the task investigated or, conversely, represent a non specific response to a widespread central nervous system damage, we included in this analysis also measures of damage of fiber bundles not directly associated to the performance of the task investigated, including the CST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because MTR decrease is more influenced by myelin loss than axonal loss. However, Davie et al (1999) found a good correlation between a reduction in NAA concentration and a reduction in MTR within MS lesions of patients who had entered the secondary progressive phase of the disease, while patients with a more benign disease course showed a relative preservation of MTR and NAA.…”
Section: Correlations With Other Mr Techniquesmentioning
confidence: 79%